Legal Protection for Government Employees with Work Agreements (PPPK) from a Human Rights Persfective in Indonesia - Ulya, Ulya; Satoto, Sukamto; Helmi, Helmi (Ipso Jure, 2025)
ASN Law changes the categorization of the State Apparatus into Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). If we associate with the form of appointment of PPPK is a work agreement for a certain period of time, then the PPPK position is implicitly a government employee who has legal force in the employment agreement. The employment agreement for PPPK is a binding legal relationship between Non-PNS government employees and the government agencies that employ it. The entry of Government Employees with Work Agreements (PPPK) as part of ASN is expected to be an accelerator in efforts to realize ASN professionalism. Some treatments to PPPK in ASN Law are not in accordance with human rights, namely principles of equality, non-discrimination, interrelation, interdependence and state responsibility. The regulation on PPPK shows the country's setback in formulating indicators for fulfillment of the right to work